Effect of Empowerment Program for Caregivers and Elderly Patients with Diabetes in Kantharawichai District, Mahasarakham Province - Rungsa, Jutharat; Rodjarkpai, Yuvadee; Pongsaengpan, Paiboon (Srinagarind Medical Journal, 2017)
Background and Objective : Diabetes is a chronic disease and cannot be cured. Elderly patients with diabetes need to be received constant care from family. The objective was to study effect of empowerment program for caregivers and elderly patients with diabetes in Kantharawichai district, Mahasarakham province. Methods: This research is a quasi-experimental study. The samples were divided into experimental group and comparison group, with each group consisted of 30 caregivers and 30 elderly patients with diabetes. The experimental group was received the empowerment program, while the comparison group was received regular service. The data were analyzed by using paired t-test and independent t-test Results: The results of study revealed as following: The experimental group had an average score of perceived empowerment, caring behavior, and health behavior of elderly patients with diabetes after intervention higher than before intervention (p<0.05) and higher than comparison group (p<0.05). The elderly patients with diabetes in the experimental group had fasting blood sugar level after intervention lower than before intervention and lower than comparison group (p<0.05). Conclusions: The results of this study would suggest that this empowerment program should be recommended for further expansion and guided to promote caring behavior and health behavior in elderly patients with diabetes for the better. ผลของโปรแกรมการเสริมสร้างพลังอำนาจของผู้ดูแลและผู้ป่วยสูงอายุโรคเบาหวาน อำเภอกันทรวิชัย จังหวัดมหาสารคาม หลักการและวัตถุประสงค์ : โรคเบาหวานเป็นการเจ็บป่วยเรื้อรัง ไม่สามารถรักษาให้หายขาดได้ ผู้ป่วยสูงอายุโรคเบาหวานมีความจำเป็นที่จะต้องได้รับการดูแลอย่างต่อเนื่องจากครอบครัว การศึกษาครั้งนี้จึงมีวัตถุประสงค์เพื่อศึกษาผลของโปรแกรมการเสริมสร้างพลังอำนาจของผู้ดูแลและผู้ป่วยสูงอายุโรคเบาหวาน อำเภอกันทรวิชัย จังหวัดมหาสารคาม วิธีการศึกษา : การศึกษาครั้งนี้เป็นการศึกษากึ่งการทดลอง กลุ่มตัวอย่างแบ่งเป็นกลุ่มทดลองและกลุ่มเปรียบเทียบ ซึ่งแต่ละกลุ่มประกอบด้วยผู้ดูแล 30 ราย และผู้ป่วยสูงอายุโรคเบาหวาน 30 ราย กลุ่มทดลองได้รับโปรแกรมการเสริมสร้างพลังอำนาจ ส่วนกลุ่มเปรียบเทียบได้รับการบริการตามปกติ เครื่องมือที่ใช้ ได้แก่ แบบสัมภาษณ์และเครื่องวัดระดับน้ำตาลในเลือด สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ paired t-test และ independent t-test ผลการศึกษา : พบว่า กลุ่มทดลองมีคะแนนเฉลี่ยการรับรู้พลังอำนาจ พฤติกรรมการดูแลผู้ป่วยสูงอายุโรคเบาหวาน และพฤติกรรมสุขภาพของผู้ป่วยสูงอายุโรคเบาหวานหลังการทดลองสูงกว่าก่อนการทดลองและสูงกว่ากลุ่มเปรียบเทียบอย่างมีนัยสำคัญทางสถิติ (p<0.05) และผู้ป่วยสูงอายุโรคเบาหวานมีระดับน้ำตาลในเลือดหลังการทดลองต่ำกว่าก่อนการทดลองและต่ำกว่ากลุ่มเปรียบเทียบอย่างมีนัยสำคัญทางสถิติ(p<0.05) สรุป : โปรแกรมการเสริมสร้างพลังอำนาจนี้เป็นอีกแนวทางในส่งเสริมพฤติกรรมการดูแลและพฤติกรรมสุขภาพในผู้ป่วยสูงอายุโรคเบาหวานให้ดีขึ้น